How Audit Reviewers Respond to an Audit Preparer's Affective Bias: The Ironic Rebound Effect - Frank, Michele L.; Hoffman, Vicky B. (The Accounting Review, 2015)
ABSTRACT Prior research suggests that audit seniors' judgments are sometimes biased by their affect toward (i.e., feeling of personally liking or disliking) client personnel. We examine how experienced audit reviewers respond when reviewing an audit preparer's judgment that appears to be biased by the preparer's affect toward a client's controller. In our experiment, reviewers are provided with a preparer's judgment that appears inconsistent with the audit workpapers. We then examine the effect of providing versus not providing reviewers with a cue about the preparer's positive or negative affect toward the controller. We find that despite reviewers' belief that affect biases a preparer's judgment, reviewers who are informed of the preparer's affect do not rely less on the preparer's judgment. Instead, they actually rely more on the preparer's judgment than do those who are not informed about the preparer's affect. This result is consistent with Wegner's (1994) ironic rebound effect, which predicts that sometimes when individuals are trying not to rely on information, they ironically rely on it more. Our findings suggest a potential limitation of the audit review process.